Braiding Inuit knowledge and Western science to understand light goose population dynamics under a changing climate - Natalie A Carter; Laura M Martinez-Levasseur; Vicky Johnston; Paul A Smith; Aupaa Irkok; Bobbie Saviakjuk; Lenny Emiktaut; null Salliq Project Management Committee; null Arviat Project Management Committee; Bhavana Chaudhary; Gita Ljubicic; Ray T Alisauskas; et al. (Ecology and Society, 2025)
Increasing abundance of Snow and Ross’s Geese ( Anser caerulescens and Anser rossii ; kangut and qaaraarjuk in Inuktut, respectively), referred to collectively as light geese, has caused alterations in various Canadian Arctic ecosystems. Inuit have harvested light geese for generations and hold knowledge that offers unique insights into the ecology and population dynamics of these species. By combining interviews with 40 light goose harvesters and Elders with results from aerial surveys in the Kivalliq region of Nunavut, we (1) describe changes in light goose distribution and abundance between the 1940s and the 2010s, (2) explore the effects of light geese on local ecosystems, and (3) identify factors driving these changes. Inuit observations gathered through lifetimes of land-based observations and results from aerial surveys concurred that (1) light goose numbers have increased regionally since the 1940s, and (2) light goose numbers decreased in several colonies within the Kivalliq region between the 1960s–1990s and the 2010s, including in two Migratory Bird Sanctuaries. Inuit have noted that habitat loss due to overgrazing and grubbing has pushed light geese to abandon altered habitats in favor of new breeding and foraging sites. Inuit observations also indicated that light geese have altered their migration behavior (how, when, and where they migrate and nest) in response to earlier spring snowmelt, the drying of ponds and lakes, and an increased number of predators. These conclusions add substantially to overall understanding about light geese in regions where aerial surveys are expensive and infrequent, and scientific studies are limited in geographic coverage.